Contradicting challenges: the complexity of documenting personal information in a regulatory environment. (11th October 2021) - Haraldsdottir, Ragna Kemp; Gunnlaugsdottir, Johanna
Abstract : Purpose: Many organizations are challenged by different and, perhaps, opposite, registration and protection obligations of information regarding their employees. The purpose of this paper is to explore how organizations balance the registration obligations of the Icelandic equal pay standard (EPS) and the protection requirements of the general data protection regulation (GDPR). It aims to raise awareness of how information professionals can ensure that documentation on the education and skills of employees is authentic, traceable and secure. Design/methodology/approach: The analytical framework covered multiple-cases and semi-structured interviews with various professionals and comprehensive documentary analysis. Findings: The findings indicate that the organizations were not properly prepared for the implementation of the EPS and were hesitant regarding further registration of personal information due to GDPR. Documentary analysis also revealed critical attitudes towards the legal endorsement of the standard and its potential success. Originality/value: There is a lack of studies explaining the juxtaposition of information and records management and the legal and regulatory environment. This paper provides a unique description of how information and recordkeeping practices function with the requirements of the EPS whilst complying with GDPR. The results could bring valuable opportunities for the information profession regarding the development, implementation, administration and maintenance of documentary evidence regarding the requirements of international and national standards and legislations and advance their collaboration with other professionals in the management of information.